A Case of Glaucoma in Hereditary Spherocytosis. Issue 12 (December 2018) - Chen, Haiying; Symons, Robert C.A.; Mayson, Eleni; Skalicky, Simon E.
Abstract : Purpose: To report a case of glaucoma and the inherited red cell membranopathy hereditary spherocytosis diagnosed simultaneously in 2 individuals in a family. Patient: A 66-year-old man with normal pressure glaucoma and hereditary spherocytosis. Results: This patient presented with a branch retinal vein occlusion, and normal tension glaucoma that was incidentally detected. Further history revealed that the patient's maternal grandmother also had hereditary spherocytosis and glaucoma. Conclusions: We hypothesize that glaucoma and hereditary spherocytosis may be associated. Hereditary spherocytosis may be a potential risk factor for glaucoma by causing impaired blood supply to the optic nerve.